Experimental study of water evaporation of sessile droplets on a solid substrate with different thermal conductivities - Borodulin Vladimir; Letushko Vladimir; Nizovtsev Michail; Sterlyagov Alexey (MATEC Web of Conferences, 2017)
The results of experimental studies of water evaporation of sessile droplet on solid substrates with different thermal conductivities are presented. In experiments during droplet evaporation the temperature of its surface was determined using the infrared thermography method. The obtained results showed that interfacial temperature was higher than the adiabatic evaporation temperature for all substrates. As thermal conductivity of the substrate decreased, the droplet temperature decreased and the evaporation lifetime increased significantly. As a result it was established that the thermal conductivity of the material has a significant effect on the evaporation of droplets.